Effects Of Radiation Therapy On Estrogen And Oxidative Stress In Postmenopausal Women With Breast Cancer - DR.G.J.BELWALKAR,; DR. D. BADAKH,; DR.P.E.JAGTAP,; DR. P.N. PUJARI, (International Journal of Pharma and Bio Sciences, 2012)
Breast cancer is one of the most common neoplastic diseases of women. Estrogen and oxidative stress play an important role in carcinogenesis of breast cancer. Radiation has long been used for treatment of breast cancer. During radiation therapy, free radicals are generated which result into an oxidative stress. Estrogen, MDA, SOD & vitamin E were estimated in 50 postmenopausal women with breast cancer before and after radiation therapy and in 30 healthy controls. The results showed that estrogen were increased before therapy but decreased following therapy. The levels of MDA were elevated in patients before and after therapy. SOD and vitamin E were low before and after therapy. We hypothesize that radiation is destroying tumor cells directly due to this mechanism of excessive oxidative stress is formed during radiation. The more reduced SOD and vitamin E after radiotherapy interprets the utilization of existing antioxidant system for defending the additional oxidative stress.